(untitled) (Geneva, 1973)
Recommendations of the report stress the importance of quality control, packaging, and reliability of supplies; suggest promotion measures (including the possibility of joint promotion bodies in major markets), and marketing strategies.
Keywords: Trái cây, sấy khô,Fruit, dried; Tiếp thị,Marketing